Assessment of the effectiveness and efficiency of the economic community of West African States Medicines Regulatory Harmonization initiative by the pharmaceutical industry - Owusu-Asante, Mercy; Darko, Delese Mimi; Walker, Stuart; Salek, Sam (Frontiers in Pharmacology, 2023)
Background: Following the establishment of Economic Community of West African States Medicines Regulatory Harmonization (ECOWAS-MRH) initiative in 2017, it was considered timely to carry out an evaluation of the current status of the initiative’s operating model by the pharmaceutical industry users. This study examined the challenges being encountered and identified strategies that would strengthen the ECOWAS-MRH initiative moving forward. Methods: The Process Effectiveness and Efficiency Rating (PEER) questionnaire was used to collect data from manufacturers who have submitted applications to the joint assessment procedure and had identified recommendations for improving the performance of the ECOWAS-MRH initiative. Results: Ten pharmaceutical manufacturer participants (innovator, generic foreign, generic local) all reported that harmonisation of registration requirements was a major benefit, allowing submission of the same dossier to multiple countries, reducing the application burden and saving time and resources. Additionally, receipt of the same list of questions from several countries enables the compilation of a single response package, resulting in shorter timelines for approvals compared to the individualised country responses. Another benefit of a harmonised registration process was the simultaneous accessibility of medicines in various markets. Key challenges included a lack of centralised submission and tracking, differences in regulatory performance of the national medical regulatory authorities, a lack of detailed information for applicants and a low motivation to use the ECOWAS-MRH route with a preference for other regulatory pathways in the ECOWAS member states. Conclusion: This study identified several approaches to increase the effectiveness of this initiative: the implementation of risk-based approaches such as use of reliance pathways; establishment of a robust information technology systems, building assessor capacity to facilitate processing and monitoring applications; and priority review of ECOWAS-MRH products.